Fragment profiling of low molecular weight heparins using reversed phase ion pair liquid chromatography-electrospray mass spectrometry. (30th April 2015) - Xu, Xiaohui; Li, Daoyuan; Chi, Lequan; Du, Xuzhao; Bai, Xue; Chi, Lianli
Abstract: Low molecular weight heparins (LMWHs) are linear and highly charged carbohydrate polymers prepared by chemical or enzymatic depolymerization of heparin. Compared to unfractionated heparin (UFH), LMWHs are prevalently used as clinical anticoagulant drugs due to their lower side effects and better bioavailability. The work presented herein provides a rapid and powerful fragment mapping method for structural characterization of LMWHs. The chain fragments of two types of LMWHs, enoxaparin and nadroparin, were generated by controlled enzymatic digestion with each of heparinase I (Hep I, Enzyme Commission (EC) # 4.2.2.7), heparinase II (Hep II, no EC # assigned) and heparinase III (Hep III, EC # 4.2.2.8). Reversed phase ion pair high performance liquid chromatography (RPIP-HPLC) coupled with electrospray ion trap time-of-flight mass spectrometry (ESI-IT-TOF-MS) was used to profile the oligosaccharide chains ranging from disaccharides to decasaccharides. A database containing all theoretical structural compositions was established to assist the mass spectra interpretation. The six digests derived by three enzymes from two types of LMWHs exhibited distinguishable fingerprinting patterns. And a total of 94 enoxaparin fragments and 109 nadroparin fragments were detected and identified. Besides the common LMWH oligosaccharides, many components containing characteristic LMWH structures such as saturatedl -idopyranosuronic acid, 2, 5-anhydro-d -mannitol, 1, 6-anhydro-d -aminopyranose, as well as odd number oligosaccharides were also revealed. Quantitative comparison of major components derived from innovator and generic nadroparin products was presented. This approach to profile LMWHs' fragments offers a highly reproducible, high resolution and information-rich tool for evaluating the quality of this category of anticoagulant drugs or comparing structural similarities among samples from various sources. Graphical abstract: Highlights: A fingerprinting approach was established for evaluating the sequence of LMWHs. New software was developed to interpret the complicated MS data of LMWH fragments. This method is capable to detect special and characteristic LMWH structures. A total of 94 enoxaparin fragments and 109 nadroparin fragments were identified. Quantitative comparison between innovator and generic nadroparin were made.